THE IMPORTANCE AND SCIENTIFIC SIGNIFICANCE OF LEARNING ENGLISH IN COLLABORATION IN ENGLISH TEACHING - Saodat Yokubjonova Avazbek kizi; Dadamirzayeva Barno Otamirza kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Innotation: This article is dedicated to study of the important aspects of the influence of cooperative education on the classroom environment. Cooperative learning encourages active student participation, teamwork, and communication. In addition, cooperative learning activities provide opportunities for language and science teachers to develop interdisciplinary connections.